ASSESSING STUDENTS’ METALINGUISTIC AWARENESS: THE ABILITY TO DETECT AMBIGUITY - Misesani, Dian (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
The purpose of this research was to investigate English learners’ metalinguistic awareness on detecting lexical ambiguity in a text. In ddition, it also investigated whether or not the participants’ interests in certain linguistics branches are influential in analyzing an article. This was a case study design aiming to inveestigate in depth and detailed data source collected from students’ assessment.The finding showed that most of the participants can retrieve their metalinguistic awareness and linguistic knowledge. Specifically, half of them could detect ambiguity because of the influence of their interest in semantics. Moreover, a few of those who were interested in semantics could analyze through both semantics and pragmatics view. In this way, it can be concluded that the participants’ interests in semantics was influential in detecting ambiguity as a domain of semantics. This research suggests that in studying linguistics, students should not only be taught about theories but also how to analyze either written or spoken discourse on the basis of those theories in linguistics branches.